2019
DOI: 10.1101/680504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteolytic queues at ClpXP increase antibiotic tolerance

Abstract: Antibiotic tolerance is a widespread phenomenon that renders antibiotic treatments less effective and facilitates antibiotic resistance. Here we explore the role of proteases in antibiotic tolerance, short-term population survival of antibiotics, using queueing theory (i.e. the study of waiting lines), computational models, and a synthetic biology approach. Proteases are key cellular components that degrade proteins and play an important role in a multi-drug tolerant subpopulation of cells, called persisters. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 66 publications
(74 reference statements)
3
34
0
Order By: Relevance
“…The higher persistence levels during ciprofloxacin treatment could be due to double-stranded DNA breaks caused by ciprofloxacin activating the SOS response (44) (the SOS response is directly related to persistence). We also observed that despite controlling methodology to the greatest extent possible, persister levels varied considerably (far more than observed in our previous work with E. coli) (7) between experiments for both streptomycin and ciprofloxacin treatments (Table S1). We hypothesize that this variability might be due to the stochastic fluctuations (noise) in gene expression levels, which results in protein level variations significantly even among genetically identical cells in a similar environment (45).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The higher persistence levels during ciprofloxacin treatment could be due to double-stranded DNA breaks caused by ciprofloxacin activating the SOS response (44) (the SOS response is directly related to persistence). We also observed that despite controlling methodology to the greatest extent possible, persister levels varied considerably (far more than observed in our previous work with E. coli) (7) between experiments for both streptomycin and ciprofloxacin treatments (Table S1). We hypothesize that this variability might be due to the stochastic fluctuations (noise) in gene expression levels, which results in protein level variations significantly even among genetically identical cells in a similar environment (45).…”
mentioning
confidence: 54%
“…Among them, proteases and associated chaperons are notable persister-related genes because overexpression and knockouts of these genes alter persistence levels (14,35). Furthermore, our lab recently demonstrated that interfering with protein degradation by forming a proteolytic queue at ClpXP will increase tolerance levels dramatically and in a tunable fashion (larger queues caused higher tolerance) (7). Research over the last several years has resulted in a lot of discussion concerning genes essential for persistence (8,13,26,29).…”
mentioning
confidence: 99%
“…Two advantages of this method are it allows for concentration of cells while minimizing time for RNA degradation, and we recover any whole cells present after antibiotic treatment regardless of viability (this includes cells that are considered "viable but not culturable" (VBNC), see Methods). This work builds off our previously reported results with antibiotic tolerance, and uses a similar setup with the same strains of E. coli 29 . The sequencing data was analyzed using DESeq and based on this analysis, we consider significant changes in gene expression to be greater than two-fold with an adjusted p-value <0.1.…”
Section: Resultsmentioning
confidence: 89%
“…Our findings show that many of the regulatory proteins activated during antibiotic stress are regulated by protein degradation. Protein aggregation was recently demonstrated in persister cells 25 , and our previous work shows that interfering with degradation at the protease ClpXP increases antibiotic tolerance in E. coli 29 . To confirm that the transcriptional changes are due to altered proteolysis, we then sequenced populations with slowed protein degradation using our previously established system 29 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation